2002
DOI: 10.1016/s0896-6273(02)00781-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Striate Cortical Activation during Spatial Attention

Abstract: Recordings of event-related potentials (ERPs) and event-related magnetic fields (ERMFs) were combined with functional magnetic resonance imaging (fMRI) to study visual cortical activity in humans during spatial attention. While subjects attended selectively to stimulus arrays in one visual field, fMRI revealed stimulus-related activations in the contralateral primary visual cortex and in multiple extrastriate areas. ERP and ERMF recordings showed that attention did not affect the initial evoked response at 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
210
4
7

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(270 citation statements)
references
References 46 publications
45
210
4
7
Order By: Relevance
“…This model accommodates two key observations: (i) it explains the relative enhancement of neural activity at attended locations, and how selectivity can be flexibly rerouted to favor new locations; and (ii) it explains the seeming paradox that attentional modulations in higher level areas appear earlier than in lower level areas (10,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 64%
“…This model accommodates two key observations: (i) it explains the relative enhancement of neural activity at attended locations, and how selectivity can be flexibly rerouted to favor new locations; and (ii) it explains the seeming paradox that attentional modulations in higher level areas appear earlier than in lower level areas (10,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 64%
“…Because neural responses in the early visual areas are relatively insensitive to the repetition effect compared with those in the later visual areas Schacter and Buckner, 1998), the confounding of early visual signals into MEG data in the present study would obscure the NA effect occurring in higher visual areas. Given recent studies reporting that V1 area receives a delayed feedback signal from the higher visual cortex at a latency of 190 -230 msec (Noesselt et al, 2002;Halgren et al, 2003) in addition to the primary visual input from the thalamus, it would be difficult to exclude the early visual signals on the basis of signal latency. We therefore presented visual stimuli based on our random dot blinking (RDB) technique developed previously (Okusa et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Why are these effects commonly observed with fMRI but not with other techniques? Recent studies that have combined the high spatial resolution of fMRI with the high temporal resolution of EEG and magnetoencephalography (Noesselt et al, 2002) have demonstrated that the effects of attention on V1 activity do not take place during the initial stimulusrelated response (ϳ60 -90 msec). Instead, longer-latency activity (in the time range of 150 -250 msec) was found to be strongly modulated by attention.…”
Section: The Effect Of Attention On Sensory Processingmentioning
confidence: 99%